PENGGUNAAN NA-CMC DAN GUM XANTHAN UNTUK MEMPERBAIKI KUALITAS CAKE BERAS RENDAH LEMAK - Widija, Stephanie Livia Joana; Trsinawati, Chatarina Yayuk; Widjajaseputra, Anna Ingani (Widya Mandala Surabaya Catholic University, 2017)
The use of Na-CMC need to be combined with xanthan gum hydrocolloid to improve the physical, chemical, and sensory properties of reduced fat rice cake. The research aimed to determine the effect of hydrocolloid concentration (Na-CMC and xanthan gum = 4:1) onphysical, chemical, and sensory properties of reduced fat rice cake. The experimental design was Randomized Block Design with one factor, namely hydrocolloid concentration, which consisted of five levels: 1%, 2%, 3%, 4%, and 5% based on flour weight with five replications. Data were analyzed by Analysis of Variance at α = 5 % to determine the effect of treatment on the physical, chemical, and sensory properties of reduced fat rice cake, and followed by Duncan's Multiple Range Test at α = 5 % to determine differences between treatment levels. The results showed that hydrocolloid concentration gave significant effects on moisture content, specific volume, hardness, cohesiveness, gumminess, chewiness and sensory properties (preference to pore uniformity, ease of chewing, tenderness, taste, and moistness), but didn’t give a significant effect on springiness of reduced fat rice cake. Reduced fat rice cake with hydrocolloid concentration of 4% is the most preferred cake by consumers.